Factors Hindering Green Building Performance: A Review (Sains Humanika, 2016)
The demand for green buildings in the property market is substantially increasing. The motivation for the investment on green buildings ranges from environmental concerns and social benefits to financial savings during the operational stage. However, these perceived benefits have been argued to be mostly theoretical and yet to be empirically proven. There is often a performance gap between the expected and the actual measured performance of green buildings once operational. Green buildings simply fail to perform as to what it was intended despite the thorough design and technological considerations put at the initial stage of their development. Hence, by reviewing various literatures, this paper targets to indicate and discuss the factors that hinder green buildings from achieving their fullest performance potential. Six theoretical factors namely miscommunication, technologies used, modeling tools, construction process and handover, occupant behavior and management and control were identified from various literatures. The findings in this paper will be a commencement for further studies pertaining to non-performance of green buildings.Â
Keywords: Green building; performance